KONSEP IJTIHAD PROGRESIF ABDULLAH SAED DALAM MENGATASI PROBLEMATIKA KONTEMPORER - Afifullah Afifullah (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2016)
In the history of Islamic civilization, Islam once ruled the world with the rapid development of science and both naqli aqli discovered and developed by Muslim scholars. The development of science reaches its zenith at the time of Abbasiyah dynasty centered in Baghdad (Iraq). The success achieved by Muslim scholars at the time it was not a coincidence, but derived from hard work and sincerity of Muslim scholars at the time. However, with the passing of time the development of science in the Muslim world was decline, compared with Europe rapidly developing science (renaissance). Along with the decline of science in the Muslim world today makes Abdullah Saeed think hard to provide a solution to this problem, so he offered a progressive Islamic ideas with progressive methods ijtihadis, so that science in the Islamic world back to the point of its greatness